PERANCANGAN ALAT PEMBELAH KELAPA DENGAN DUA MATA PISAU - Zainuddin; Azmy, Ilham; Fhaisol, Muhammad Iqbal; Londa, Petrus (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Coconut is massively consumed by people due to its high nutrition. The coconut splitting process usually conventionally performed by empty-handed which tends to high time-consumed and less safety. In this work, coconut splitter was successfully designed by involving tool concept planning, part elements designation, and tool assembly. Tool concept planning consists of design formulation, calculation and selection of machine elements such as frame, splitting cutter, belt, pulley, shaft, and prime motor. The design process was carried out by using computer-aided design Solidworks. The design result has dimension of 860x760x700 mm with two cutters feature using circular saw and wheel which inserted to transmission system V-belt and pulley driven by motor of 2,6 kW with velocity of 332 rpm to achieve 600 pieces coconut splitting per hour. The design of coconut splitter is highly expected to enhance productivity and safety while coconut splitting process.